Leadership Perceptions in Collaborative Marketing Groups: Cases from the Southern Philippines - Montiflor, M.; Axalan, J.; Lamban, R.; Real, R.; Concepcion, S.; Batt, Peter; Murray-Prior, Roy; Rola-Rubzen, Maria Fay (International Society of Horticultural Science, 2013)
Numerous smallholder vegetable farmers in the Southern Philippines have been organized into clusters or collaborative marketing groups. The purpose of these clusters is to gain production, marketing and capacity building support, consolidate produce for higher value markets, deliver in bulk to save on transport and transaction costs, and to increase household income. One of the factors influencing the ability of the clusters to achieve these goals is leadership. Using the case study method, this study looks at the leadership traits of cluster leaders in Bukidnon, South Cotabato and Davao City. A total of 35 smallholder farmers from the three areas were interviewed using a structured questionnaire. The research showed that the clusters have trusted leaders. The members have high regard towards their leaders. Their definition of an ideal leader fits the description of their current leaders. The members also trust their leaders to represent them in transactions and meetings.